Photograph of Reverend William Patrick and Standard Bearers, 1939
Black and white photograph taken outdoors, inscription on back of photo: "The Rev. William E. Patrick. Burton Covel (With Flag) 1939. ______ - Crucifer" (no name given for man on left.)